Knowledge and practices about zoonotic tuberculosis prevention and associated determinants amongst livestock workers in Nigeria; 2015 (2018)
Zoonotic tuberculosis (TB) is a significant public health disease, but has long been neglected. Information on knowledge and practices of its prevention and influencing factors amongst occupationally exposed individuals is required for designing all-inclusive, informed control programmes. We investigated knowledge and practices related to zoonotic TB prevention and associated determinants amongst herdsmen and abattoir workers in southwestern, south-eastern and north-western Nigeria using semi-structured questionnaire. Data were analysed with STATA 12. A total of 510 respondents (196 herdsmen; 314 abattoir workers) participated in the survey, of which 58.6% and 46.9% respectively were knowledgeable and demonstrated good practices about zoonotic TB prevention. Almost 60% knew that zoonotic TB transmission was preventable and 49.8% knew transmission could be through consumption of infected animal products. However, only 16.7% knew the disease could be transmitted by aerosol. Just 49.4% sought medical check-up when ill, 37.8% used protective clothing and only 29.2% usually condemned TB infected cattle. Respondents with post-primary education were about three times more likely to be knowledgeable (OR = 2.70, 95%CI: 1.68±4.33) and two times more likely to demonstrate good practice (OR = 2.23, 95%CI: 1.45±3.42) than those without formal education. Similarly, abattoir workers were about 6.4 times more likely to be knowledgeable (OR: 6.39, 95%CI: 4.31±9.47) and two times more likely to demonstrate good practice (OR: 2.03, 95%CI: 1.40±2.92) than the herdsmen. There were important knowledge gaps with poor practices about zoonotic TB prevention amongst livestock workers in Nigeria. Strong predictors of knowledge and practice were being an abattoir worker and having post-primary education. Well-designed grassroots enlightenment programmes addressing modes of transmission, handling infected cattle and seeking medical check-up are urgently needed among high risk settings considering the recently launched Road Map for Zoonotic Tuberculosis which resonates that every tuberculosis case counts towards 2030 End-TB Strategy.